Peningkatan Hasil Belajar PPKn melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas VIII.B SMPN 1 Aikmel Semester I Tahun Pelajaran 2021/2022 - Hukman, Ali (Lembaga Yasin AlSys, 2021)
The learning approach with the STAD type cooperative learning model (Student Teams Achievement Divisions) is a learning concept that helps teachers relate the material being taught to students' real-world situations and encourages students to make connections between their knowledge and its application in their lives as family and community members. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of student activities working and experiencing, not transferring knowledge from teacher to student. A learning strategy is far more important than a result. The purpose of this classroom action research (CAR) is to find out the extent to which student learning outcomes in Pancasila and Citizenship Education (PPKn) are improved by applying the STAD (Student Teams Achievement Divisions) cooperative learning model. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken it is proven to be able to improve student learning outcomes by achieving ideal standards. From 75% in the first cycle, it can increase in the second cycle to 87%. The results of this action research indicate that the application of learning with the STAD type cooperative learning model (Student Teams Achievement Divisions) can increase student learning mastery in Civics lessons with completeness reaching 87%.